SELF DEFENSE MECHANISMS IN OBESITY AS REFLECTED IN MEG CABOT’ SIZE 12 IS NOT FAT (A PSYCHOLOGICAL ANALYSIS) (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
This study is aimed at explaining the main character’s personality as reflected in the story, the obesity problem in terms of the main character's psychology and the process of self defense mechanim in the main character’s psychological problem as reflected in Meg Cabot’ Size 12 Is Not Fat.The writer employed Meg Cabot’s Size 12 Is Not Fat as the object of this study. This study is a descriptive qualitative study based on the theory of psychological analysis and new criticism theory as the approaches. It is a descriptive qualitative research since each data is in the form of words, phrases, sentences, narrations and dialogues. The data are collected by reading the novel and references dealing with the topic analysis. The data then written in descriptive and in order to answer the research questions. The investigation of this research resulted in several findings. From the analysis it may be concluded that first, dealing with the obesity problem, the main character’s personality is described as an irritable and rude person. Second, obesity as the main character’s problem has affected her psychological conditions. On the one hand the main character tried to be confident with her new body size, but on the other hand, she felt desperate with her body. Third, the writer found that the self defense mechanism worked in the main character’s psychological problem.